Exploring the performance of Australian construction industry in a recent global recession - Olatunji, Oluwole (Korean Institute of Engineering and Management, 2011)
Abstract: Available data on the recent global financial crisis (GFC) show that it lasted between the second quarter (Q2) of 2007 and the fourth quarter (Q4) of 2009. Australia is one of the first economies to fully recover from this crisis. This study explores the role played by the Australian construction industry in stimulating economic growth during the recession. In order to investigate the macro-variability trend during the financial crisis, data were collected and analysed relating to the quarterly GDP of Australia and selected countries between Q1 2000 and Q4 2009. Specifically, changes in the construction industry’s GDP were compared with aggregate GDP changes in Australian economy and similar indices in the ‘Group of 7’ (G7) countries and Organisation for Economic Co-operation and Development (OECD) countries. Moreover, specific attention was focused on Germany, France, Japan, United States of America (USA) and United Kingdom (UK). Graphical and Pearson’s correlation methods were used to analyse the relationships between changes in construction GDP and Australia’s overall economic growth during the recession. In addition, an attempt was made to develop a regression model for predicting economic growth during the recent recession using changes in gross fixed capital formation (GFCF), changes in construction GDP and the impact of these changes on national economy. Analysis shows a slight contraction in construction activities during the crisis; however construction triggered significant growth in the economy during the crisis period and afterwards. This appears to be the major difference between Australia and other major economies that have experienced a longer recession.